‘Is the modernity of Chinese art comparable? An opening of a theoretical space’ - John Clark (Journal of Art Historiography, 2014)
The expansion of the art market and in some ways ‘Western’ art cultural obsession with the way modern Chinese art has entered the world since the early 1980s has overshadowed many issues critical for modern art historiography concerning both China and its place in a modern Asian art. Is Chinese modern art of one kind, and does it have a similar conceptual and empirical topology to other modernities in Asia? Can we examine how these art cultures face the same issues over time? I examine the similarity between Asian cases such as China and Thailand and indicate some of the ways in which an Asian modernity in art can be mapped that is relatively independent of Euramerican types or models.